The insects of the inflorescences of neotropical palms (Arecaceae): diversity and coevolution - Delgado, Cesar (2026)
Introduction: Palms hold a significant position in the Amazonian flora. This study examines the insects associated with the inflorescences of various genera and species of neotropical palms, with a focus on those of local or national economic significance in the countries studied (Brazil, Ecuador, Peru). Objective: To characterize the entomological community and analyze the diversity of insects in several species and genera of neotropical palm trees, and to demonstrate the coevolutionary relationships between insects and palm trees. Methods: The study was conducted between 1990 and 2020, in the Brazilian, Ecuadorian, and Peruvian Amazon, in the Atlantic Forest of Brazil, and in the Peruvian Andes. Several thousand insects were collected in plastic bags or with an entomological net on the inflorescences of selected palm trees and anesthetized with insecticides. The insects were classified into families. A significant part was prepared on entomological pins, referenced, and sent to specialists for identification. Species new to science were described whenever possible. Results: Consistent with previous studies, it is confirmed that the Nitidulidae (Mystropini) and Curculionidae (Derelomini) families are specialists in palm inflorescences. Additionally, among hemipterans, the families Miridae (Phylini) and Thaumastocoridae (Discocoris), as well as Staphylinidae beetles, exhibit a high degree of specialization. In contrast, the Dynastidae (Cyclocephala genus) and Apidae (Trigoninae), frequently cited as palm pollinators, are not specialized and should be considered as opportunistic. Conclusion: The specific-level analysis presented here shows that a close coevolutionary relationship exists between certain insect species and specific genera or species of palms.